Comparative performance analysis and complementary triode based CMFB circuits for fully differential class AB symmetrical OTAs with low power consumption. (31st July 2015) - Centurelli, Francesco; Monsurrò, Pietro; Trifiletti, Alessandro
Summary: In this paper we extend the figures of merit for class AB symmetrical OTAs to the fully differential case and compare topologies from the literature. This analysis shows that the power consumption of the CMFB can have a significant role in determining the efficiency of the OTA, but on the other hand a CMFB is needed both to set the desired output common mode voltage and to improve the CMRR. We propose the complementary triode CMFB, i.e. a triode CMFB applied both at the NMOS and PMOS current mirrors, as suitable for class AB symmetrical OTAs, and show some case studies in deep submicron CMOS technology to assess the effectiveness of the proposed solution. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : In this paper we extend the figures of merit for class AB symmetrical OTAs to the fully differential case and compare topologies from the literature, highlighting the role of the CMFB. We propose the complementary triode CMFB, i.e. a triode CMFB applied both at the NMOS and PMOS current mirrors, as suitable for class AB symmetrical OTAs, and show some case studies in deep submicron CMOS technology to assess the effectiveness of the proposed solution.